Sensory analysis of pet foods - Koppel, Kadri (My University, 2014)
Pet food palatability depends on first and foremost on the pet and is related to the pet food sensory properties such as aroma, texture, and flavor. Sensory analysis of pet foods may be conducted by humans via descriptive or hedonic analysis, pets via acceptance or preference tests, and through a number of instrumental analysis methods. Sensory analysis of pet foods provides additional information on reasons behind palatable and unpalatable foods as pets lack linguistic capabilities. Furthermore, sensory analysis may be combined with other types of information such as personality and environment factors to increase understanding of acceptable pet foods. Most pet food flavor research is proprietary and, thus, there are a limited number of publications available. Funding opportunities for pet food studies would increase research and publications and this would help raise public awareness of pet food related issues. This mini-review addresses current pet food sensory analysis literature and discusses future challenges and possibilities.
Keywords: Pet; Pet food; Companion animal; Sensory analysis; Palatability